2017
DOI: 10.1002/jcp.25448
|View full text |Cite
|
Sign up to set email alerts
|

Gating Modulation of the Tumor‐Related Kv10.1 Channel by Mibefradil

Abstract: Several reports credit mibefradil with tumor suppressing properties arising from its known inhibition of Ca currents. Given that mibefradil (Mb) is also known to inhibit K channels, we decided to study the interaction between this organic compound and the tumor-related Kv10.1 channel. Here we report that Mb modulates the gating of Kv10.1. Mb induces an apparent inactivation from both open and early closed states where the channels dwell at hyperpolarized potentials. Additionally, Mb accelerates the kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…HEK293 cells stably expressing the Kv10.1 channel [10] were kept in culture at 37°C in a humidified 5% CO 2 atmosphere in DMEM/F12 media supplemented with 10%FBS and containing zeocin 300 μM. Experiments were conducted 24 h after palting the cells on glass coverslips, as previously reported [10]. HEK293-Kv10.1 cells were kindly provided by Dr. Luis A. Pardo and Walter Stühmer.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…HEK293 cells stably expressing the Kv10.1 channel [10] were kept in culture at 37°C in a humidified 5% CO 2 atmosphere in DMEM/F12 media supplemented with 10%FBS and containing zeocin 300 μM. Experiments were conducted 24 h after palting the cells on glass coverslips, as previously reported [10]. HEK293-Kv10.1 cells were kindly provided by Dr. Luis A. Pardo and Walter Stühmer.…”
Section: Cell Culturementioning
confidence: 99%
“…Eighty percent series resistance compensation was always applied. Experiments were conducted at room temperature, as previously reported [10].…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…1), pointing out to the voltage-sensor domain as a site of action of mibefradil. 18 The exhaustive Competition-plot of CornishBowden, 19 performed between quinidine and mibefradil, along with other observations, excluded open-pore block as the mechanism underlying mibefradilinduced inactivation. Hence, we concluded that both the mibefradil inhibition of the Cole-Moore effect and its induced inactivation were the result of the drug binding within the voltage-sensor domain.…”
mentioning
confidence: 99%
“…20 Similar to our hypothesis regarding the gating modification of Kv10.1, namely that mibefradil binds to the voltagesensor domain inducing an apparent inactivation and accelerating the rate limiting transition that accompanies the passage from deep closed states to states near the open state. 17,18 It remains to be determined where on the voltage-sensor domain mibefradil binds, thus exerting the aforementioned effects, and how this relates to the particular way of communication between voltage-sensor and pore domains of Kv10.1.…”
mentioning
confidence: 99%
See 1 more Smart Citation